DOES THE PEER TEACHING MODEL HAVE A SIGNIFICANT IMPACT ON IMPROVING STUDENTS' FOOTBALL PASSING SKILLS? - Muhammad Rizky; Oman Hadiana (Universitas Muhammadiyah Kuningan, 2025)
Study This aiming For analyze the influence of the Peer Teaching learning model on deep passing skills game football for students Class VIII of SMPN 3 Kuningan . Background study show that students passing ability Still classified as low , frequent caused by the method learning less traditional​ interactive and lack of involvement active students . The research method used is experiment with One Group Pretest-Posttest Design , involving 36 students from One selected class​ through cluster random sampling. Data were collected through test Football passing accuracy (pretest and posttest) was measured from number of balls in and time implementation , then analyzed using prerequisite tests ( Shapiro-Wilk normality and Levene's Test homogeneity ) and Paired Sample t-Test hypothesis testing with SPSS. The results of the study show existence improvement significant on students' passing skills after implementation of the Peer Teaching model, with higher average posttest score tall compared to pretest. Findings This indicates that Peer Teaching is effective in increase understanding and skills technical , as well as create atmosphere learn more​ collaborative and supportive , in line with theory Study Vygotsky's social emphasis importance interaction social and guidance Friend peers . With Thus , the learning model This recommended For applied in PJOK learning to optimize mastery technique base football .